The Concept of Learning in Islam from the Educational Perspective of Ibn Khaldun's Thought - Wibawati Bermi; Sudarto Sudarto; Hartini Hartini (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2023)
This research delves into the views of Ibn Khaldun, a 14th-century Islamic scholar, regarding the concept of learning within the educational context. Ibn Khaldun emphasizes the significance of learning through direct instruction and the role of teachers in shaping students' understanding. He perceives this concept as a holistic process aimed at developing intellect, morality, and skills. The study also explores Ibn Khaldun's perspectives on teaching methods, highlighting the crucial role of interactions with scholars to eliminate confusion regarding terminology. The primary objective of this research is to unearth and analyze Ibn Khaldun's views on the concept of learning within the context of Islamic education, comparing them with Western educational concepts. The research aims to investigate Ibn Khaldun's understanding of teaching methods, the role of teachers, and the goals of learning. The research methodology involves textual analysis of Ibn Khaldun's works, such as the